HOMESCHOOLING: PILIHAN DI TENGAH KEGAGALAN SEKOLAH FORMAL - Sadid, Agus (JIV-Jurnal Ilmiah Visi, 2012)
Homeschooling is a family-based school to provide specific education but referring to national education curriculum. Homeschooling becomes an effective choice in the failure of formal school to produce qualified graduates. Having critically discussing homeschooling in a number of aspects, this article concludes (1) home schooling can be organized as a pure homeschooling, a homeschooling model which independently develop and implement curriculum without others’ assistance; instructional achievement of pure homeschooling is equalization program and (2) homeschooling with partnership which maintains cooperation with formal school in planning and implementing instruction, developing curriculum, and evaluation. The students of homeschooling with partnership follow all processes learning evaluation in mid and final semester. Homeschooling can be organized by any community or family and protected by law. It is a right choice for the children to create qualified graduates under supervision and abundant love of the family.